The boy who became Buffalo Bill : growing up Billy Cody in bleeding Kansas - Warren, Andrea (Two Lions, 2015)
Explores how the man who became the most famous entertainer of his time and a legend of the "Wild West" grew up amid a violent regional conflict that would soon tear apart the nation.